Observational aspects including weather radar for tropical cyclone monitoring (MAUSAM, 2013)
Hkkjr ekSle foKku foHkkx ¼vkbZ- ,e- Mh-½ ds iwokZuqeku izn’kZu ifj;pkstuk ¼,Q- Mh- ih-½ ds lanHkZ esa dh xbZ fofHkUu izs{k.kkRed lqfo/kkvksa vkSj rduhdksa dh leh{kk dh xbZ gSA ftudk iz;ksx pØokr ds iFk dk irk yxkus vkSj m".kdfVca/kh; pØokrksa dks le>us ds fy, fd;k tk ldrk gSA izkS|ksfxdh ds laca/k esa fd, x, iz;klksa ds okLrfod ijh{k.k ls izpkyukRed lanHkZ esa gekjs iwokZuqekuksa ds fu"iknu dk irk pyrk gSA bl laca/k esa vko’;d mik;ksa ij bl 'kks/k&i= esa fopkj&foe’kZ fd;k x;k gSAIn the context of the Forecast Demonstration Project (FDP) of the India Meteorological Department (IMD), a review is made of the various observational facilities and techniques which can be deployed, for the detection tracking and understanding of tropical cyclones.  The real test of the efforts in terms of technology is the performance of our forecasts in an operational context. The paper discusses the steps needed in this regard.